Kapital Simbolik Sebagai Identitas Keluarga Besar Studi Kasus Komunitas Bani Ma’shum di Kecamatan Jatibarang Brebes Jawa Tengah - Hanifa Maulidia (Jurnal Empirika, 2018)
This paper describes symbolic capital that owned by an extended family community, Bani Ma'shum. The theory is Bourdieu's concept of habitus, fields, and symbolic capital. This paper uses a qualitative method to explain the survival of the Bani Ma'shum community in district Jatibarang Brebes, Central of Java. This paper describe Bani Ma'shum as a large family community of Javanese ethnicity. Values and experiences based on the Javanese habitus they applied to their activity everyday. The use of the concept of bani is not just naming, but also show that Arab habitus has also been constructed into this community. Bani Ma'shum was formed in NU (ahli sunnah wal jama'ah) community. Bani Ma'shum has several capital, there are social, cultural, politic, economy, and symbolic capital. These capital play in three arenas: socio-religious, politic, and economy. From other capitals, symbolic capital is most plays as important role for members of Bani Ma'shum. Because with symbolic capital members of Bani Ma’shum can access other capital. Bani Ma'shum distinction is based on blood ties and family lineage. This family membership is only based on blood ties and not everyone can enter the Bani Ma'shum family, except by marry their child of Bani Ma'shum family.